Breaking Immunological Tolerance through OX40 (CD134) - Pratima Bansal-Pakala; Michael Croft (The Scientific World Journal)
Immunological tolerance represents a mechanism by which cells of the host remain protected from the immune system. Breaking of immunological tolerance can result in a variety of autoimmune diseases such as rheumatoid arthritis, diabetes, and multiple sclerosis. The reasons for tolerance breaking down and autoimmune processes arising are largely unknown but of obvious interest for therapeutic intervention of these diseases. Although reversal of the tolerant state is generally unwanted, there are instances where this may be of benefit to the host. In particular, one way a cancerous cell escapes being targeted by the immune system is through tolerance mechanisms that in effect turn off the reactivity of T lymphocytes that can respond to tumor-associated peptides. Thus tolerance represents a major obstacle in developing effective immunotherapy against tumors. The molecules that are involved in regulating immunological tolerance are then of interest as they may be great targets for positively or negatively manipulating the tolerance process.